A Qualitative Study of Digital Teaching Resources Integration Into University Biology Courses - Ram Martinez; Annalie Bejoc; Aimee Tabada (Journal of Research and Innovation In Open and Distance Learning, 2022)
Faculty and students of science courses at the university level are in a rapid transition from the usual face-to-face to the digital technology-based classes. The new normal teaching integrating digital technology have become burdensome to a few faculties, and yet to some it has become a challenge and quickly pursued training to learn things quickly. Unfortunately, many of the technologies has changed teaching and learning into a certain degree. This study focused on how the quality and character of teaching have been impacted by the integration of digital technology into Biology courses. Faculty and BSc Biology students were purposively selected and interviewed using an inclusion criteria. Audio-recorded interviews on Zoom transcribed manually were thematically analyzed. First cycle coding was done using Nvivo. Evaluation codes, were utilized during the second cycle coding using NVivo. Emerged codes from the evaluative perspective of the researchers and qualitative commentary provided a systematic collection of information of activities related to digital integration, characteristics and outcomes which provided judgment, improve effectiveness, and/or inform decisions about future development plans, programs, and policies. Codes were scored with corresponding magnitude. Positive/negative signs were further used to indicate whether a theme positively/negatively affected respondents, then tabulated and analyzed. The result showed that digital technology integration was significantly correlated with faculty and students’ attributes such as age, computer gaming experience. Biology courses need the essential alignment like the TPACK framework and advanced didactics. Digital technologies integration has been plainly limited the effects of teaching as conventional education models need to embrace changes brought about by the pandemic in the post-industrial decline